HISTORICAL STUDY OF THE SOCIAL SYSTEM OF THE MAURYAN PERIOD - Singh, Arvind Kumar; Parveen, Shagufta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Man is a social animal, he spends his life within the society and remains connected with the society throughout his life. A person’s birth, upbringing, education, livelihood, everything happens in the society. In this way, man and society have an interdependent relationship. In the initial stage of human life, the form of society was uncertain and undeveloped. Gradually people must have come in contact with each other and social relations were formed, as a result of which society was formed. It can also be said that society was formed as a result of people’s tendency to live together and their desire to give an organized form to life.1 The Maurya period was divided into many castes and groups, their social behavior, thoughts, lifestyle and behavior were also different from each other. Over time, due to this social division, many social institutions were formed which became the motivating factor in revealing the social life of man. Gradually, social systems related to various aspects of society were formed. These systems provided completeness to the society and led it towards development. Among these systems that provided completeness to the society was the Varna system, under this system every person got a place according to his natural qualities. The entire human society was divided into four classes according to their natural inclination and talent.2 Before this system, the Indian society was divided into Varnas by the social dimension of the Gupta period. This Varna division was the basis of the natural qualities of the person. This Varna division of the society was the basis of the social life of that time, inspired by which every person followed this social system while performing the duties prescribed for him.